2y(y-3)=27+y2

Simple and best practice solution for 2y(y-3)=27+y2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2y(y-3)=27+y2 equation:



2y(y-3)=27+y2
We move all terms to the left:
2y(y-3)-(27+y2)=0
We add all the numbers together, and all the variables
-(+y^2+27)+2y(y-3)=0
We multiply parentheses
-(+y^2+27)+2y^2-6y=0
We get rid of parentheses
-y^2+2y^2-6y-27=0
We add all the numbers together, and all the variables
y^2-6y-27=0
a = 1; b = -6; c = -27;
Δ = b2-4ac
Δ = -62-4·1·(-27)
Δ = 144
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{144}=12$
$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-6)-12}{2*1}=\frac{-6}{2} =-3 $
$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-6)+12}{2*1}=\frac{18}{2} =9 $

See similar equations:

| x/12=44 | | F(-5)=-0.25x-6 | | x+(-x)=x+3 | | F(-2.25)=-0.25x-6 | | 5x+8x=112 | | 9x−13=4x+32 | | -4n-8=4(-3n-2) | | 4+5=7+3x | | 6x+12+30=90 | | 5x+10=9x-10 | | 5n=10*2 | | (-10x-7)-(3x-10)=x | | -2(-3x+1=-14 | | -1+20y=y | | 22x-1=10 | | 3=21−3n | | 4x-3/2+-3x-5/5=-0.4=61.4/10 | | 3x+4=1x-14 | | 7n+5=68/ | | 216=6(-4m+4) | | 126=x=77 | | 30=7s−26 | | 37+19x-4=90 | | 3+x=2*3+7 | | -6p+4(8p+1)=108 | | 9c−20=16 | | 9x+5(9-5x)=3+10(3x-5) | | 16w−12=15w | | 12^2=9(9+x) | | 65=9+7g | | 25+3h=64 | | -7k2-7k-14=-8 |

Equations solver categories